Implementasi Kebijakan PermenPAN RB Nomor 17 Tahun 2021 tentang Penyederhanaan Birokrasi di Lingkungan Sekretariat Daerah Kabupaten Bandung Barat - Raden Arham Nasrulloh; Agustina Setiawan; Yovinus Yovinus (Universitas 17 Agustus 1945, 2024)
This study aims to examine the implementation of the bureaucratic simplification policy by equating administrative positions to functional positions in the West Bandung Regency Regional Secretariat. This study uses a qualitative approach with a case study method, as well as data collection techniques through in-depth interviews with key informants, main informants, and supporting informants. The results of the study indicate that the bureaucratic simplification policy has a significant impact on organizational performance, but on the other hand also faces various challenges related to communication, resources, disposition, and bureaucratic structure. These challenges include unclear information, unsynchronized budget allocation, and competency gaps that arise due to job equalization.